Pengaruh Gaya Hidup Terhadap Penyakit Hipertensi Berdasarkan Teori TPB (Theory Of Planned Behavior) - Melviani Melviani; Saftia Aryzki; Agenia Rahman; Gina Aima Putri; Setia D. R. Riadi (LPPM Universitas Sari Mulia, 2022)
Hypertension in general can be interpreted as a disease of high blood pressure. This condition can lead to various health complications that are life-threatening while increasing the risk of heart disease, stroke, and even death. Theory of Planned Behavior or TPB Theory of Planned Behavior (TPB) is one theory that has been widely applied in various fields of behavioral research. The research method using descriptive analytic observational. The population in this study were 77 community respondents in the Manarap Baru area, RT.03, Banjar Regency, aged 45-65 years. Data were taken using a questionnaire and analyzed univariately with the software version. The results of the research that have been carried out include the characteristics of the respondents and special data including knowledge, Attitude toward Behavior (attitudes) with 77 respondents stating that they agree with a healthy lifestyle. 76 respondents stated that the factors that cause high blood pressure are factors in old age. 74 respondent sanswered that the thing that prevents a person from suffering from high blood pressure is not smoking, eating a low-salt diet. Subjective Norm 65 out of 77 respondents agreed that according to my neighbors eating high-fat meat more than three times a week can increase high blood pressure. 39 out of 77 respondents agreed that according to my friend when eating adding soy sauce, extra salt and sauce when eating increases blood pressure. Perceived Behavioral Control Respondents 70 answered that the respondent's behavioral control was 94.61% good. The results of the measurement values owned by the respondents in accordance with the questionnaire based on the Theory of Planned Behavior related to compliance and proper use of hypertension drugs including knowledge and attitudes were good as many as 74 people (96.1%) and 3 people (3.9%).